Dead laws for dead men: the politics of federal coal mine health and safety legislation - Curran, Daniel J. (Pittsburgh, 1993)
"This account of the struggle for coal mine health and safety legislation in the U.S. examines the series of laws that steadily expanded the role of the federal government from the late 1800s through the 1980s. Curran concludes that federal legislation has done little to improve change conditions in the coal mines."